Risk factors for peripherally inserted central catheter line–related deep venous thrombosis in critically ill intensive care unit patients. (June 2020) - Bhargava, M; Broccard, S; Bai, Y; Wu, B; Dincer, EH; Broccard, A
Introduction: Central venous access using peripherally inserted central catheters is frequently used for patients receiving intravenous medications in the hospital or outpatients. Although there are several benefits of peripherally inserted central catheters, such as ease of insertion, low procedure-related risk and higher patient satisfaction, there are complications associated with peripherally inserted central catheter use. Despite some studies evaluating peripherally inserted central catheter line–related complications, the factors associated with peripherally inserted central catheter–related deep venous thrombosis in critically ill medical-surgical patients are poorly described. The objective of this case-control study was to identify the risk factors associated with peripherally inserted central catheter line–related deep venous thrombosis in critically ill medical-surgical intensive care unit patients in a community hospital. Methods: We abstracted relevant clinical data from 21 cases with symptomatic peripherally inserted central catheter–related deep venous thrombosis and 42 controls with peripherally inserted central catheters but no deep venous thrombosis. Results: Of the factors evaluated, female gender, the use of triple lumen peripherally inserted central catheters, larger outer diameter, and open (vs valve) peripherally inserted central catheters were associated with venous thrombosis. In this retrospective study, we did not identify any association of peripherally inserted central catheter–related deep venous thrombosis with a prior history of deep venous thrombosis, use of alteplase, antiplatelet therapy, prophylactic or therapeutic anticoagulation, international normalized ratio, platelet count and the use of peripherally inserted central catheters for total parenteral nutrition. Conclusion: Our study indicates that the catheter size relative to the diameter of the vein could be an important risk factor for the development of peripherally inserted central catheter–related deep venous thrombosis. The study findings should be confirmed in a larger study designed to identify risk factors of peripherally inserted central catheter–related deep venous thrombosis. In the meantime, the peripherally inserted central catheter lines should be used judiciously in critically ill patients.